An artistic narrative inquiry into the representations of artists during the Egyptian revolution and how their experience can promote reform - Nawar, Dalia (Kansas State University, 2023)
This research is an artistic narrative investigation of the representations of artists during the Egyptian Revolution (ER) and how their experiences can inspire transformation. It explores art educators' perspectives on contemporaneity and art literacy. Three interviews were conducted with each of the five participants using arts-informed narrative inquiry approaches. During the 2011 Egyptian Revolution, three of them were active graffiti artists. My participants’ stories revealed narrative patterns about the evolving purpose of graffiti during ER, the complex relationships within the faculty, ethical practices, and biases, modernizing the curriculum and identity issues, the abandonment of voice, rejecting art labeling and categorization, aesthetic appreciation and its significance in human life, and the implications of skill loss in post-college life. The findings from the research demonstrate the complexities of Egypt's fine arts program, as well as the importance of experience as a vehicle for change and reform.
Keywords: Egyptian revolution; Fine art education; Narrative inquiry; Arts-informed research